Emission reduction and market encroachment: Whether the manufacturer opens a direct channel or not?. (1st October 2020) - Zhang, Li-Hao; Yao, Jie; Xu, Lang
Abstract: This paper investigates the equilibrium strategies considering abatement decision and manufacturer encroachment in a supply chain, in which the manufacturer is a Stackelberg leader and the retailer is a follower. The manufacturer first determines the channel structure to distribute products through only the retail channel structure, only the direct channel structure, or the dual-channel structure. After that, the manufacturer and the retailer sequentially decide to sell a low-carbon product or a common product. The optimal prices, order quantities and profits under different combinations of channel structure and abatement decision are characterized. We observe that both firms prefer to invest in emission abatement under a sole channel structure if consumers have eco-friendly preference, while the equilibrium emission abatement strategies for the dual-channel structure depend on the investment cost coefficient and revenue-sharing coefficient. Under encroachment, the manufacturer is always better off while the retailer is worse off except for selling low-carbon product through the direct channel with a high consumer's eco-friendly preference. In addition, when the consumer's eco-friendly preference is moderate, selling low-carbon product may be a scourge for the retailer if the manufacturer has an encroachment ability. Further, the manufacturer should always post the direct channel's order quantity after observing the retail channel's order quantity under the dual-channel structure.